Selected Lectures of the Course “Take care of children”, 3rd Edition; Cagliari (Italy); October 30, 2021 - Various Authors, --- (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2021)
Selected Lectures of the Course “Take care of children”, 3rd Edition • PRENDERSI CURA DEI BAMBINI CON LA FITOTERAPIA E GLI INTEGRATORI ALIMENTARI • ISTRUZIONE PER L’USO, OPPORTUNITÀ E LIMITI • Cagliari (Italy) • October 30th, 2021 The Course has been organized with the patronage of SIN (Italian Society of Neonatology). LECT 1. PRESENTATION OF THE COURSE “TAKE CARE OF CHILDREN: TAKING CARE OF CHILDREN WITH PHYTOTHERAPY AND DIETARY SUPPLEMENTS. OPPORTUNITIES AND LIMITATIONS” [PRESENTAZIONE DEL CORSO “TAKE CARE OF CHILDREN: PRENDERSI CURA DEI BAMBINI CON LA FITOTERAPIA E GLI INTEGRATORI ALIMENTARI. OPPORTUNITÀ E LIMITI] • V. Fanos, G. Trapani (Cagliari and Sanremo, Italy) LECT 2. NUTRITION IN THE FIRST 1,000 DAYS OF LIFE [LA NUTRIZIONE NEI PRIMI 1.000 GIORNI] • A. Dessì, A. Bosco, R. Pintus (Cagliari, Italy) LECT 3. HEALTHY NUTRITION IMPROVES IMMUNE REACTIVITY [UNA CORRETTA NUTRIZIONE MIGLIORA LA REATTIVITÀ IMMUNITARIA] • G. Trapani (Sanremo, Italy) LECT 4. PLANTS AND PLANT EXTRACTS ACTIVE ON THE IMMUNE SYSTEM [PIANTE ED ESTRATTI VEGETALI ATTIVI SUL SISTEMA IMMUNITARIO] • O. Al Jamal (Cagliari, Italy) LECT 5. FOOD SUPPLEMENTS FOR THE IMMUNE SYSTEM [INTEGRATORI ALIMENTARI PER IL SISTEMA IMMUNITARIO] • D. Careddu (Novara, Italy) LECT 6. GOOD SLEEP CAN MANAGE IMMUNE REACTIONS [UN BUON SONNO È IN GRADO DI GESTIRE LE REAZIONI IMMUNITARIE] • A. Arrighi (Montevarchi, Italy) LECT 7. ADEQUATE PHYSICAL ACTIVITY MAKES THE IMMUNE SYSTEM MORE EFFICIENT [UN’ATTIVITÀ FISICA ADEGUATA RENDE PIÙ EFFICIENTE IL SISTEMA IMMUNITARIO] • D. Meleleo (Canosa di Puglia, Italy) LECT 8. LOW-DOSE CYTOKINES. PRINCIPLES AND EVIDENCE OF A NEW PHARMACOLOGICAL TREND [CITOCHINE A BASSO DOSAGGIO. PRINCIPI ED EVIDENZE DI UN NUOVO TREND FARMACOLOGICO] • G. Bona (Novara, Italy)